평창-정선 일대 “행매층”의 분포와 층서적 의의 - 김남수(Namsoo Kim); 최성자(Sung-Ja Choi); 송윤구(Yungoo Song); 박채원(Chaewon Park); 최위찬(Ueechan Chwae); 이기욱(Keewook Yi) (자원환경지질, 2020)
The stratigraphical position of the Haengmae Formation can provide clues towards solving the hot issue on the Silurian formation, also known as Hoedongri Formation. Since the 2010s, there have been several reports denying the Haengmae Formation as a lithostratigraphic unit. This study aimed to clarify the lithostratigraphic and chronostratigraphic significance of the Haengmae Formation. The distribution and structural geometry of the Haengmae Formation were studied through geologic mapping, and the correlation of relative geologic age and the absolute age was performed through conodont biostratigraphy and zircon U-Pb dating respectively. The representative rock of the Haengmae Formation is massive and yellow-yellowish brown pebble-bearing carbonate rocks with a granular texture similar to sandstone. Its surface is rough with a considerable amount of pores. By studying the mineral composition, contents, and microstructure of the rocks, they have been classified as pebble-bearing clastic rocks composed of dolomite pebbles and matrix. They chiefly comprise of euhedral or subhedral dolomite, and rounded, well-sorted fine-grained quartz, which are continuously distributed in the study area from Biryong-dong to Pyeongan-ri. Bedding attitude and the thickness of the Haengmae Formation are similar to that of the Hoedongri Formation in the north-eastern area (Biryong-dong to Haengmae-dong). The dip-direction attitudes were maintained 340°/15° from Biryong-dong to Haengmae-dong with a thickness of ca. 200 m. However, around the southwest of the studied area, the attitude is suddenly changed and the stratigraphic sequence is in disorder because of fold and thrust. Consequently, the formation is exposed to a wide low-relief area of 1.5 km × 2.5 km. Zircon U-Pb age dating results ranged from 470 to 449 Ma, which indicates that the Haengmae Formation formed during the Upper Ordovician or later. The pebble-bearing carbonate rock consisted of clastic sediments, suggesting that the Middle Ordovician conodonts from the Haengmae Formation must be reworked. Therefore, the above-stated evidence supports that the geologic age of the Haengmae Formation should be Upper Ordovician or later. This study revealed that the Haengmae Formation is neither shear zone, nor an upper part of the Jeongseon Limestone, and is also not the same age as the Jeongseon Limestone. Furthermore, it was confirmed that the Haengmae Formation should be considered a unit of lithostratigraphy in accordance with the stratigraphic guide of the International Commission on Stratigraphy (ICS). 행매층은 실루리아기 회동리층과 오르도비스기 정선층(정선석회암) 사이에 위치하고 있어, 행매층의 층서적 위치는 회동리층의 존재와 시층서적 논란을 해결하는데 결정적 정보를 제공할 수 있다. 2011년 이후부터 행매층 존재와 함께 암층서 단위가 될 수 있는지에 대하여 논란이 있어왔다. 따라서 본 연구에서는 비룡동-평안리 사이 지역에 대한 정밀 지질조사를 통하여 행매층 분포와 지질구조 특성을 규명하고, 생층서와 절대연령 결과를 대비하여 행매층의 암층서 및 시층서적 의의를 정의하였다. 행매층을 대표하는 암석은 괴상의 황색-황갈색 함력 탄산염암으로 사암과 같은 입상조직을 가지고 있으며 노두 표면이 매우 거칠고 기공이 많이 발달하고 있다. 구성광물의 조성, 함량 및 미세조직 특징을 근거로 볼 때, 행매층의 특성은 역질의 쇄설암으로, 역은 돌로마이트이며 기질은 자형 및 반자형의 돌로마이트와 원마도 및 분급이 좋은 미사질의 석영이 주구성광물로 이루어져있다. 행매층은 조사지역인 정선군 정선읍 용탄리(비룡동)에서 평창군 미탄면 평안리까지 측방으로 연속하여 잘 발달하고 있을 뿐만 아니라 일정한 두께를 가지고 분포하고 있다. 행매층의 층리, 태위 및 층후는 비룡동-행매동 사이 지역에서는 회동리층과 거의 비슷하게 발달하나, 행매동 남서쪽에서는 등사습곡과 충상단층에 의하여 외견상 불규칙한 분포양상을 보인다. 즉 비룡동-행매동 사이에서는 340°±10°/15°의 태위를 유지하면서 200 m 층후로 발달하지만, 평안리 백암 일대에서는 동-서 1.5 km, 남-북 2.5 km에 달하는 넓은 면적을 차지하고 있다. 행매층 내 쇄설성 저어콘 U-Pb 연령은 470-450 Ma 범위를 갖고 있어 행매층의 최대 퇴적시기는 후기 오르도비스기를 지시한다. 또한, 행매층을 구성하는 함력 탄산염암은 쇄설성 퇴적암이므로, 행매층에서 분류된 중기 오르도비스기 코노돈트 화석군은 재퇴적된 이지성을 의미한다. 이는 행매층의 지질시대가 중기 오르도스기 이후 임을 지시한다. 본 연구 결과, 행매층은 전단대일 뿐이며, 정선석회암의 일부이고, 정선석회암과 동일한 시기를 갖는다는 부정적 학설은 타당성을 잃었으며, 행매층은 국제층서위원회(ICS)에서 제시한 층서기준에 적합하게 잘 정의된 암층서 단위임이 확인되었다.